Narrazione e intercultura: un incontro cruciale - Franco Cambi (Firenze University Press, 2010)
Bruner argues that narrative is the original paradigm of thought. It underlies the exercise of the mind through the construction of stories to the real. It is the «narrative thinking» that arises, then, logical thinking, scientific, metaphysical. Through the story the man has always given rise to exchanges of thought and life in every civilization and culture. The narrative also has a formative function and educational level intercultural because it helps to understand the difference in humanity. The author offers thoughts on narrative as a cognitive style and as a type of textuality.